Preparation method of high-strength regenerated aluminum alloy

By detecting and classifying the components of scrap aluminum, combining the synergistic effect of specific refining agents and argon, and adding deteriorating agents, the problem of poor performance of existing recycled aluminum alloys is solved, and high-strength and low-cost recycled aluminum alloy preparation is achieved, which is suitable for the manufacturing of shock absorbing towers for automobile body structural parts.

CN119640074APending Publication Date: 2025-03-18DELTA ALUMINUM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411376695.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing recycled aluminum alloys are difficult to meet the performance requirements of high tensile strength, yield strength, etc. of shock absorbing towers of automobile body structural parts. At the same time, due to the direct heating and smelting of scrap aluminum that is not classified and recycled, the production cost is high and the material performance is not ideal.

Method used

Waste aluminum was detected and classified by photoelectric direct reading spectrometer, silicon-containing waste aluminum was selected as the raw material, and a specific refining agent and argon gas were used to synergize, and deteriorating agent was added to improve the tensile strength and yield strength of the recycled aluminum alloy while improving thermal stability.

Benefits of technology

The preparation of high-strength recycled aluminum alloy is realized, the tensile strength, yield strength and after-break elongation are improved, the thermal stability is improved, and the production cost is reduced. It is suitable for the manufacturing of shock absorbing towers for automotive body structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of a high-strength regenerated aluminum alloy. A regenerated aluminum alloy liquid used in the preparation method comprises the following components in percentage by mass: 1.0-4.5% of copper, 8.0-13.0% of silicon, 0.30-1.50% of magnesium, less than or equal to 1.5% of zinc, less than or equal to 0.50% of iron, less than or equal to 0.10% of manganese, less than or equal to 0.014% of nickel, less than or equal to 0.124% of titanium, less than or equal to 0.01% of lead, less than or equal to 0.006% of tin, less than or equal to 0.021% of chromium and the balance of aluminum and impurities, and the total content of the impurities is less than or equal to 0.3%. According to the high-strength regenerated aluminum alloy, the thermal stability percentage elongation after fracture A is larger than or equal to 3.5%, the tensile strength is larger than 250 MPa, the yield strength Re is larger than 170 MPa, the overall mechanical property is excellent, the performance requirement of an automobile body structural part can be met, waste aluminum is used as the raw material of the regenerated aluminum alloy, and the use cost of automobile parts can be greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloys, and particularly relates to a method for preparing a high-strength recycled aluminum alloy. Background Art

[0002] Recycled aluminum alloy refers to aluminum alloy materials that are remanufactured by recycling waste aluminum products through smelting, purification and alloying. The production and use of this material has significant advantages in environmental protection and economy, because it reduces the demand for primary aluminum resources, saves energy, reduces greenhouse gas emissions, and effectively utilizes waste aluminum products.

[0003] With the development of the automobile industry, the performance requirements of cast aluminum alloys used in shock towers for automobile body structural parts are becoming higher and higher. At present, some automobile companies require cast aluminum alloys used in shock towers for automobile body structural parts to have higher requirements on tensile strength, yield strength and other properties. However, it is difficult for the current recycled aluminum alloys to meet the above requirements, which limits the application market of recycled aluminum alloys. At the same time, the existing technology does not classify the waste aluminum and directly heats and melts it, so the composition of the waste aluminum is complex. In order to achieve the target composition of the recycled aluminum alloy, the conventional practice is to dilute the composition of the recycled aluminum alloy liquid by adding a large amount of pure aluminum. This practice will greatly increase the production cost of the recycled aluminum alloy and make the recycled aluminum alloy lose its market competitiveness.

[0004] In order to obtain high-performance recycled aluminum alloy in the prior art, the recycled aluminum alloy liquid is usually subjected to a refinement and modification treatment, mainly by adding aluminum-titanium series refiners to refine the α-Al grains and adding strontium to modify the eutectic Si phase. Since the recycled aluminum alloy liquid usually contains transition elements, and the transition elements have a toxic effect on the grain refining effect of the aluminum-titanium series refiners, the grain refining effect is reduced, and the mechanical properties of the recycled aluminum alloy are not ideal.

[0005] Therefore, there is an urgent need for a method for preparing high-strength recycled aluminum alloy. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a high-strength recycled aluminum alloy.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-strength recycled aluminum alloy, the preparation method comprising the following steps: (1) Using a photoelectric direct reading spectrometer to detect and classify the composition of scrap aluminum, and selecting scrap aluminum whose main alloying element is silicon as the raw material for recycled aluminum alloy; using a crusher to crush the scrap aluminum into scrap aluminum blocks, and then using a magnetic separator to magnetically separate and remove iron from the crushed scrap aluminum to obtain pre-treated scrap aluminum; (2) The pre-treated scrap aluminum is heated and melted at 760-780°C, and a photoelectric direct reading spectrometer is used for sampling, and the composition is detected online, and the insufficient composition is compensated so that the recycled aluminum alloy liquid includes the following components by mass percentage: copper 1.0-4.5%, silicon 8.0-13.0%, magnesium 0.30-1.50%, zinc ≤1.5%, iron ≤0.50%, manganese ≤0.10%, nickel ≤0.014%, titanium ≤0.124%, lead ≤0.01%, tin ≤0.006%, chromium ≤0.021%, and the remainder is aluminum and impurities, of which the total impurity content is not more than 0.3%; (3) Control the furnace temperature to 720-740°C, evenly discharge the refining agent and high-purity argon gas into the alloy furnace, and maintain for 15-20 minutes to obtain the regenerated aluminum alloy liquid after slag removal and degassing; (4) Control the furnace temperature to 760°C-770°C, add a modifier to the regenerated aluminum alloy liquid after slag removal and degassing, and keep it for 20-30 minutes to obtain a regenerated aluminum alloy liquid with refined modification; (5) The refined and modified recycled aluminum alloy liquid is allowed to stand for 40 to 60 minutes and then cast into recycled aluminum alloy.

[0008] Furthermore, the amount of the modifier added is 0.4-0.6% of the mass of the recycled aluminum alloy liquid.

[0009] Furthermore, the modifier includes the following components in mass percentage: 4-7% Na 2 SO 4 , 11~13%NaCl, 7~10%Na 3 AlF 6 , 16~19%K 2 TiF 6 , 8~10%K 2 ZrF, 5~7%Ce, the balance is Na 3 PO 4 .

[0010] Furthermore, the particle size of Ce is between 600 mesh and 1000 mesh.

[0011] In order to improve the mechanical properties of the recycled aluminum alloy, further, the mass ratio of copper, silicon and magnesium is 2~3:10~12:1.

[0012] When using scrap aluminum as raw material to prepare recycled aluminum alloy, although the scrap aluminum has been processed through multiple procedures, its impurity content is often relatively high, and it is difficult to achieve the impurity content of less than 0.15% usually required to ensure a higher tensile strength. Or if this standard is to be met, more pretreatment steps are usually required, and the cost will increase significantly. The recycling of scrap aluminum goes against the original intention of environmental protection and energy saving. The present invention adds a modifier on the basis of the composition of the recycled aluminum alloy liquid to improve the tensile strength of the recycled aluminum alloy. The modifier is added to the recycled aluminum alloy liquid, Na 2 SO 4 , NaCl, Na 3 AlF 6 , K 2 TiF 6 , K 2 ZF 6 These components, as the core of the modifier, promote the morphological change and refinement of silicon and copper phases by reacting with the elements in the alloy. The excellent nucleation core of α-Al in the aluminum alloy generated by the reaction can have a significant refinement effect on the aluminum alloy; the modifier can transform silicon from the hard and brittle needle-shaped or flake-shaped β~Si (FeSiAl) to finer, dispersed particles or short rods, which can reduce the formation and propagation of cracks; at the same time, it inhibits the formation of coarse θ' (CuAl 2 ) phase, promoting fine and uniform precipitation; Ce, as a rare earth element, can effectively refine the grains, and Ce can also combine with impurities to purify the alloy, and the remaining Na 3 PO 4 It can be used as a flux to help other modifier components to be better dispersed in the molten alloy, promote the modification effect, and the synergistic effect of multiple components to improve the tensile strength of the alloy. At the same time, under this condition, the yield strength of the recycled aluminum alloy is improved. However, it is found that the thermal stability of the aluminum alloy is not ideal after adding the modifier.

[0013] Furthermore, the refining agent comprises the following components in parts by weight: 3-5 parts of zinc chloride, 9-12 parts of potassium fluoroaluminate, 13-16 parts of carbon powder, 10-15 parts of lithium chloride, 7-10 parts of calcium fluoride and 8-12 parts of potassium fluoroborate.

[0014] Furthermore, 8-10 kg of refining agent is added to each ton of recycled aluminum alloy liquid for each refining, each refining takes 15-25 minutes, and the refining frequency is 3-4 times.

[0015] Furthermore, the amount of argon is 5~6m 3 / h, the rotor speed is 570~600r / min, and the gas working pressure is 0.2~0.3MPa.

[0016] The present invention improves the thermal stability of aluminum alloy by using a specific refining agent and argon gas in synergy. First, the present invention uses a specific refining agent and the addition of argon gas to better purify the melt and reduce the impact of high-content impurities. At the same time, a large number of bubbles formed during the refining process help to serve as heterogeneous nucleation points during the cooling process to promote grain refinement. Smaller grains mean more grain boundaries, and grain boundaries can hinder the movement of dislocations, thereby improving the thermal stability of the material. At the same time, fine grains also help to improve the plastic deformation ability of the material, that is, the elongation after fracture.

[0017] Furthermore, the particle size of the waste aluminum blocks is less than 10 mm.

[0018] Furthermore, scrap aluminum includes discarded parts of automobile aluminum products, discarded aluminum core wires, and discarded cans.

[0019] Furthermore, the casting temperature is 680-700°C, the casting speed is 180-220kg / min, and the cooling water quenching effect is 100-120 tons / h.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The recycled aluminum alloy of the present invention has high tensile strength, yield strength and elongation after fracture, high thermal stability and good welding effect, and can be used to prepare shock towers for automobile body structural parts.

[0021] 2. The present invention adds a modifier on the basis of the composition of the recycled aluminum alloy liquid, which can improve the tensile strength of the recycled aluminum alloy; at the same time, under this condition, the yield strength of the recycled aluminum alloy is improved.

[0022] 3. The present invention improves the thermal stability of the aluminum alloy and increases the elongation after fracture by using a specific refining agent and argon gas in synergy. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 This embodiment provides a method for preparing a high-strength recycled aluminum alloy, the preparation method comprising the following steps: (1) Using a photoelectric direct reading spectrometer to detect and classify the composition of scrap aluminum, and selecting scrap aluminum whose main alloying element is silicon as the raw material for recycled aluminum alloy; using a crusher to crush the scrap aluminum into scrap aluminum blocks, the particle size of the scrap aluminum blocks is less than 10 mm; then using a magnetic separator to magnetically separate and remove iron from the crushed scrap aluminum to obtain pre-treated scrap aluminum; the scrap aluminum is discarded parts of automobile aluminum products; (2) The pretreated scrap aluminum is heated and melted at 770°C, and a photoelectric direct reading spectrometer is used for sampling, and the composition is detected online, and the insufficient composition is compensated so that the recycled aluminum alloy liquid includes the following components in mass percentage: copper 1.8%, silicon 10.4%, magnesium 1.0%, zinc 1.2%, iron 0.34%, manganese 0.04%, nickel 0.014%, titanium 0.074%, lead 0.01%, tin 0.004%, chromium 0.016%, and the remainder is aluminum and impurities, of which the total impurity content is 0.29%; (3) Control the furnace temperature to 730°C, evenly discharge the refining agent and high-purity argon into the alloy furnace, and maintain for 17 minutes to obtain the regenerated aluminum alloy liquid after slag removal and degassing; the refining agent includes the following components by weight: 4 parts of zinc chloride, 10 parts of potassium fluoroaluminate, 14 parts of carbon powder, 12 parts of lithium chloride, 8 parts of calcium fluoride and 9 parts of potassium fluoroborate; 9 kg of refining agent is added to each ton of regenerated aluminum alloy liquid for each refining, and each refining takes 20 minutes, and the number of refining times is 4 times. The amount of argon used is 5.5m 3 / h, the rotor speed is 590r / min, and the working pressure of the gas is 0.25MPa; (4) The furnace temperature is controlled to 765°C, and a modifier is added to the regenerated aluminum alloy liquid after slag removal and degassing, and the temperature is maintained for 25 minutes to obtain a regenerated aluminum alloy liquid subjected to refinement and modification. The modifier comprises the following components in mass percentage: 6% Na 2 SO 4 , 12%NaCl, 9%Na 3 AlF 6 , 17%K 2 TiF 6 , 9%K 2 ZrF, 6%Ce, balance Na 3 PO 4 The particle size of Ce is between 600 mesh and 1000 mesh; the amount of the modifier added accounts for 0.5% of the mass of the recycled aluminum alloy liquid; (5) The refined and modified recycled aluminum alloy liquid was allowed to stand for 50 minutes and then cast at 695°C. The casting conditions were: casting temperature of 690°C, casting speed of 200kg / min, and 110 tons / h of cooling water quenching to obtain recycled aluminum alloy.

[0025] Example 2 This embodiment provides a method for preparing a high-strength recycled aluminum alloy, the preparation method comprising the following steps: (1) Using a photoelectric direct reading spectrometer to detect and classify the composition of scrap aluminum, and selecting scrap aluminum whose main alloying element is silicon as the raw material for recycled aluminum alloy; using a crusher to crush the scrap aluminum into scrap aluminum blocks, the particle size of the scrap aluminum blocks is less than 10 mm; then using a magnetic separator to magnetically separate and remove iron from the crushed scrap aluminum to obtain pre-treated scrap aluminum; the scrap aluminum is discarded parts of automobile aluminum products; (2) The pretreated scrap aluminum is heated and melted at 760°C, and a photoelectric direct reading spectrometer is used for sampling, and the composition is detected online, and the insufficient composition is compensated so that the recycled aluminum alloy liquid includes the following components by mass percentage: copper 1.6%, silicon 10%, magnesium 1.0%, zinc ≤1.5%, iron 0.34%, manganese 0.02%, nickel 0.008%, titanium 0.114%, lead 0.004%, tin 0.006%, chromium 0.013%, and the remainder is aluminum and impurities, of which the total impurity content is 0.3%; (3) Control the furnace temperature to 720°C, evenly discharge the refining agent and high-purity argon into the alloy furnace, maintain for 15 minutes, and obtain the regenerated aluminum alloy liquid after slag removal and degassing; the refining agent includes the following components by weight: 3 parts of zinc chloride, 9 parts of potassium fluoroaluminate, 13 parts of carbon powder, 10 parts of lithium chloride, 7 parts of calcium fluoride and 8 parts of potassium fluoroborate; 8 kg of refining agent is added to each ton of regenerated aluminum alloy liquid for each refining, and the refining time is 15 minutes each time, and the refining frequency is 3 times. The amount of argon used is 5m 3 / h, the rotor speed is 570r / min, and the working pressure of the gas is 0.2MPa; (4) The furnace temperature is controlled to 760°C, and a modifier is added to the regenerated aluminum alloy liquid after slag removal and degassing, and the temperature is maintained for 20 minutes to obtain a regenerated aluminum alloy liquid subjected to refinement and modification. The modifier comprises the following components in mass percentage: 4% Na 2 SO 4 , 11% NaCl, 7~10% Na 3 AlF 6 , 16%K 2 TiF 6 , 8%K 2 ZrF, 5%Ce, balance Na 3 PO 4 The particle size of Ce is between 600 mesh and 1000 mesh; the amount of the modifier added accounts for 0.4% of the mass of the recycled aluminum alloy liquid; (5) The refined and modified recycled aluminum alloy liquid was allowed to stand for 40 minutes and then cast at 690°C. The casting conditions were: casting temperature of 680°C, casting speed of 180kg / min, and quenching with 100 tons / h of cooling water to obtain the recycled aluminum alloy.

[0026] Example 3 This embodiment provides a method for preparing a high-strength recycled aluminum alloy, the preparation method comprising the following steps: (1) Using a photoelectric direct reading spectrometer to detect and classify the composition of scrap aluminum, and selecting scrap aluminum whose main alloying element is silicon as the raw material for recycled aluminum alloy; using a crusher to crush the scrap aluminum into scrap aluminum blocks, the particle size of the scrap aluminum blocks is less than 10 mm; then using a magnetic separator to magnetically separate and remove iron from the crushed scrap aluminum to obtain pre-treated scrap aluminum; the scrap aluminum is discarded parts of automobile aluminum products; (2) The pretreated scrap aluminum is heated and melted at 780°C, and a photoelectric direct reading spectrometer is used for sampling, and the composition is detected online to compensate for the insufficient composition, so that the recycled aluminum alloy liquid includes the following components by mass percentage: copper 1.9%, silicon 11%, magnesium 1.0%, zinc 1.2%, iron 0.20%, manganese 0.05%, nickel 0.010%, titanium 0.11%, lead 0.01%, tin 0.005%, chromium 0.016%, and the remainder is aluminum and impurities, of which the total impurity content is 0.26%; (3) Control the furnace temperature to 740°C, evenly discharge the refining agent and high-purity argon gas into the alloy furnace, maintain for 20 minutes, and obtain the regenerated aluminum alloy liquid after slag removal and degassing; the refining agent includes the following components by weight: 5 parts of zinc chloride, 12 parts of potassium fluoroaluminate, 16 parts of carbon powder, 15 parts of lithium chloride, 10 parts of calcium fluoride and 12 parts of potassium fluoroborate; 10 kg of refining agent is added to each ton of regenerated aluminum alloy liquid for each refining, each refining takes 25 minutes, and the number of refining times is 4 times. The amount of argon gas used is 6m 3 / h, the rotor speed is 600r / min, and the working pressure of the gas is 0.3MPa; (4) The furnace temperature is controlled to 770°C, and a modifier is added to the regenerated aluminum alloy liquid after slag removal and degassing, and the temperature is maintained for 30 minutes to obtain a regenerated aluminum alloy liquid subjected to refinement and modification. The modifier comprises the following components in percentage by mass: 7% Na 2 SO 4 , 13%NaCl, 10%Na 3 AlF 6 , 19%K 2 TiF 6 , 10%K 2 ZrF, 7% Ce, balance Na 3 PO 4 The particle size of Ce is between 600 mesh and 1000 mesh; the amount of the modifier added accounts for 0.6% of the mass of the recycled aluminum alloy liquid; (5) The refined and modified recycled aluminum alloy liquid was allowed to stand for 60 minutes and then cast at 700°C. The casting conditions were: casting temperature of 700°C, casting speed of 220kg / min, and 120 tons / h cooling water quenching condition to obtain recycled aluminum alloy.

[0027] Comparative Example 1 The difference between this comparative example and Example 1 is that the recycled aluminum alloy liquid includes the following components in mass percentage: 2.8% copper, 8.4% silicon, 2.0% magnesium, 1.2% zinc, 0.34% iron, 0.04% manganese, 0.014% nickel, 0.074% titanium, 0.01% lead, 0.004% tin, 0.016% chromium, and the remainder is aluminum and impurities, with a total impurity content of 0.29%.

[0028] Comparative Example 2 The difference between this comparative example and Example 1 is that the raw aluminum alloy liquid includes the following components in mass percentage: 0.8% copper, 11.4% silicon, 1.0% magnesium, 1.2% zinc, 0.34% iron, 0.04% manganese, 0.014% nickel, 0.074% titanium, 0.01% lead, 0.004% tin, 0.016% chromium, and the remainder is aluminum and impurities, wherein the total impurity content is 0.29%.

[0029] Comparative Example 3 The difference between this comparative example and Example 1 is that the raw aluminum alloy liquid includes the following components in mass percentage: 3.8% copper, 7.4% silicon, 1.0% magnesium, 2.2% zinc, 0.34% iron, 0.04% manganese, 0.014% nickel, 0.074% titanium, 0.01% lead, 0.004% tin, 0.016% chromium, and the remainder is aluminum and impurities, wherein the total impurity content is 0.29%.

[0030] Comparative Example 4 The difference between this comparative example and Example 1 is that the refining agent comprises the following components in parts by mass: 8 parts of zinc chloride, 6 parts of potassium fluoroaluminate, 10 parts of carbon powder, 16 parts of lithium chloride, 13 parts of calcium fluoride and 4 parts of potassium fluoroborate.

[0031] Comparative Example 5 The difference between this comparative example and Example 1 is that 15 kg of refining agent is added to each ton of recycled aluminum alloy liquid for each refining, each refining takes 20 minutes, and the refining frequency is 4 times.

[0032] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of argon used is 7m 3 / h, the rotor speed is 500r / min, and the working pressure of the gas is 0.15MPa.

[0033] Comparative Example 7 The difference between this comparative example and Example 1 is that the modifier includes the following components in mass percentage: 11% Na 2 SO 4 , 6%NaCl, 16%Na 3 AlF 6 , 10%K 2 TiF 6 , 2%K 2 ZrF, 3% Ce, balance Na 3 PO 4 .

[0034] Comparative Example 8 The difference between this comparative example and Example 1 is that the casting conditions are: a casting temperature of 670°C, a casting speed of 250kg / min, and a cooling water quenching condition of 130 tons / h to obtain a recycled aluminum alloy.

[0035] Comparative Example 9 The difference between this comparative example and Example 1 is that the particle size of Ce is between 200 mesh and 500 mesh.

[0036] Performance Testing The mechanical properties of the recycled aluminum alloys of Examples 1-3 and Comparative Examples 1-9 were measured.

[0037] (1) Mechanical properties test: Referring to GB / T228.1-2010, the room temperature mechanical properties of this test were tested on an AG-X 100kN electronic universal testing machine.

[0038] (2) Thermal stability test: The test method is carried out in accordance with GB / T228.1-2010. All aluminum alloys are tested using a 50 mm gauge extensometer, a tensile speed of 5 mm / min, a holding temperature of 150°C, and a holding time of 100 hours.

[0039] (3) Welding strength determination: refer to GB / T 2651-2008, calculation method of welding strength coefficient: welding strength coefficient = tensile strength after welding / tensile strength of parent material before welding.

[0040] The results are shown in Table 1.

[0041] Table 1 Performance test results

[0042] From the above performance test results, it can be seen that Examples 1 to 3 have high tensile strength, yield strength, elongation after break, and good thermal stability, especially Example 1 has the most outstanding comprehensive performance, which is mainly due to the synergistic effect of various steps.

[0043] However, the comparative examples did not adopt the necessary technical solutions, resulting in that their corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the composition ratio of the recycled aluminum alloy liquid was changed, and it can be seen that the comprehensive effect of the recycled aluminum alloy was reduced, proving that the synergistic effect of the composition ratio scheme of the recycled aluminum alloy liquid has an important influence on the performance effect. Comparative examples 2-3 show that the recycled aluminum alloy can obtain higher mechanical properties only when copper, silicon and magnesium are within a certain ratio range. Changes in the ratio of copper, silicon and magnesium will directly affect the microstructure and phase composition of the aluminum alloy, thereby significantly affecting its tensile strength and overall mechanical properties. In Comparative Examples 4-6, the use of the synergistic use of refining agent and argon gas is not used. From the results, it can be seen that the thermal stability and elongation of the recycled aluminum alloy are affected. The composition of the modifier in Comparative Example 7 has an effect on the tensile strength and yield strength. Comparative Example 8 shows that the recycled aluminum alloy liquid subjected to refinement and modification treatment obtained by the specific ratio of various components in the present invention can obtain better performance under specific casting conditions. The injection pressure and time affect the speed and pressure of the aluminum alloy liquid entering the mold, the fluidity of the alloy and the formation of pores and shrinkage cavities during solidification. The temperature and cooling time affect the cooling speed of the alloy liquid, and then affect the degree of grain refinement and the uniformity of the microstructure. The optimization of the casting process is adjusted for the specific alloy formula and product design of the present invention to ensure that the alloy liquid solidifies quickly and evenly in the mold to form the required microstructure. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0044] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength recycled aluminum alloy, characterized in that: The preparation method comprises the following steps: (1) Using a photoelectric direct reading spectrometer to detect and classify the composition of scrap aluminum, and selecting scrap aluminum whose main alloying element is silicon as the raw material for recycled aluminum alloy; using a crusher to crush the scrap aluminum into scrap aluminum blocks, and then using a magnetic separator to magnetically separate and remove iron from the crushed scrap aluminum to obtain pre-treated scrap aluminum; (2) The pre-treated scrap aluminum is heated and melted at 760-780°C, and a photoelectric direct reading spectrometer is used for sampling, and the composition is detected online, and the insufficient composition is compensated so that the recycled aluminum alloy liquid includes the following components by mass percentage: copper 1.0-4.5%, silicon 8.0-13.0%, magnesium 0.30-1.50%, zinc ≤1.5%, iron ≤0.50%, manganese ≤0.10%, nickel ≤0.014%, titanium ≤0.124%, lead ≤0.01%, tin ≤0.006%, chromium ≤0.021%, and the remainder is aluminum and impurities, of which the total impurity content is not more than 0.3%; (3) Control the furnace temperature to 720-740°C, evenly discharge the refining agent and high-purity argon gas into the alloy furnace, and maintain for 15-20 minutes to obtain the regenerated aluminum alloy liquid after slag removal and degassing; (4) Control the furnace temperature to 760°C-770°C, add a modifier to the regenerated aluminum alloy liquid after slag removal and degassing, and keep it for 20-30 minutes to obtain a regenerated aluminum alloy liquid with refined modification; (5) The refined and modified recycled aluminum alloy liquid is allowed to stand for 40 to 60 minutes and then cast into recycled aluminum alloy.

2. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The amount of the modifier added accounts for 0.4-0.6% of the mass of the recycled aluminum alloy liquid.

3. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The modifier includes the following components in mass percentage: 4-7% Na2SO4, 11-13% NaCl, 7-10% Na3AlF6, 16-19% K2TiF6, 8-10% K2ZrF, 5-7% Ce, and the balance is Na3PO4.

4. The method for preparing a high-strength recycled aluminum alloy according to claim 3, characterized in that: The particle size of Ce is between 600 mesh and 1000 mesh.

5. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The refining agent comprises the following components in parts by weight: 3-5 parts of zinc chloride, 9-12 parts of potassium fluoroaluminate, 13-16 parts of carbon powder, 10-15 parts of lithium chloride, 7-10 parts of calcium fluoride and 8-12 parts of potassium fluoroborate.

6. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: 8-10 kg of refining agent is added to each ton of recycled aluminum alloy liquid for each refining, each refining lasts 15-25 minutes, and the refining frequency is 3-4 times.

7. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The amount of argon gas is 5~6m 3 / h, the rotor speed is 570~600r / min, and the gas working pressure is 0.2~0.3MPa.

8. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The particle size of the scrap aluminum block is less than 10 mm.

9. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: Scrap aluminum includes discarded parts of automotive aluminum products, discarded aluminum core wires, and discarded cans.

10. The method for preparing a high-strength recycled aluminum alloy according to claim 1, characterized in that: The casting conditions are: a casting temperature of 680-700°C, a casting speed of 180-220kg / min, and a cooling water quenching condition of 100-120 tons / h.